The Demand for Leisure and Money - Phlips, Louis (Econometrica, 1978)
This chapter discusses demand for leisure and the transactions demand for money that is imbedded in a demand system derived from a specified utility function. The Stone–Geary utility function is dynamized by the introduction of state variables as parameters. The differential equation for money shows that it has a special feature. Short-run effects are derived using the first-order conditions together with the budget constraint and the state equations. Long-run demand equations are obtained by substituting the conditions into the first-order conditions and imposing the budget constraint. There is a real need for a theory of demand in which the word income designates what it suggests, that is, the sum of labor and nonlabor income, and in which labor income depends both on the wage rate and on the number of hours worked or not worked.